Pengaruh Adopsi Teknologi Digital, Dukungan Pemerintah, Dan Literasi Keuangan Terhadap Keberlangsungan Usaha Pedagang Pasar Besar Malang - Syiva Indana; Mohammad Rizal; Muhammad Tody Arsyianto (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This research seeks to analyze and determine the influence of digital technology adoption, government support, and financial literacy on the business sustainability of traders at Pasar Besar Malang. This study employed quantitative methods and a Likert scale as a measurement tool. The sample used a purposive sampling technique, with 100 respondents, namely traders at Pasar Besar Malang. Primary data were obtained through direct questionnaire distribution using Google Forms and printed questionnaires. Testing in this study used validity, reliability, normality, classical assumption tests, multiple linear regression, and hypothesis testing using SPSS 25 software. The results of this study indicate that digital technology adoption, government support, and financial literacy each have a partial effect on business sustainability. Keywords: Digital Technology Adoption, Government Support, Financial Literacy, Business Sustainability.